The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1037/fam0000168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of economic hardship: Testing the family stress model over time.

Abstract: The current study evaluated connections between marital distress, harsh parenting, and child externalizing behaviors in line with predictions from the Family Stress Model (FSM). Prospective, longitudinal data came from 273 mothers, fathers, and children participating when the child was 2, between 3 to 5, and 6 to 10 years old. Assessments included observational and self-report measures. Information regarding economic hardship and economic pressure were assessed during toddlerhood, and parental emotional distre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
189
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 244 publications
(234 citation statements)
references
References 46 publications
18
189
0
10
Order By: Relevance
“…For example, the current study replicates results utilizing the same sample but extending offspring age into emerging adulthood (Conger & Conger, 2002; Conger et al, 2010), as well as those that have studied these associations with the offspring and their next generation child. For example, Neppl, et al (2016) found that pathways of the Family Stress Model operated in a similar fashion when the offspring from the current study became parents themselves. The current investigation also extends work conducted by others.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…For example, the current study replicates results utilizing the same sample but extending offspring age into emerging adulthood (Conger & Conger, 2002; Conger et al, 2010), as well as those that have studied these associations with the offspring and their next generation child. For example, Neppl, et al (2016) found that pathways of the Family Stress Model operated in a similar fashion when the offspring from the current study became parents themselves. The current investigation also extends work conducted by others.…”
Section: Discussionmentioning
confidence: 60%
“…Similarly, Ponnet (2014) investigated financial stress and found that parental depressive symptoms, parental conflict, and parenting mediated the association between financial stress and adolescent problem behavior. Many studies utilizing the Family Stress Model use cross-sectional data (Conger et al, 2010) or omit certain pathways of the model such that they may include harsh parenting but not marital conflict (see Neppl, et al, 2016). Thus, the current study extends research by including all family related pathways of the Family Stress Model, specifically examining how economic pressure in early adolescence influences family processes in middle adolescence and drinking behaviors into emerging adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been established that family level conflict influences parenting behaviors during long-term contextual pressures (Barajas-Gonzalez & Brooks-Gunn, 2014;Neppl, Senia, & Donnellan, 2016). For instance, families who have children that suffer from chronic pain indicate higher levels of conflict, and lower levels of cohesion (Palermo, Valrie, Karlson, 2014).…”
Section: Family Environment: Cohesion Conflict and Achievement Oriementioning
confidence: 99%